A proposal of visual assessment of serotonergic deficits in parkinsonian syndromes: An 123I-FP-CIT SPECT study - Tomoko Totsune; Toru Baba; Yoko Sugimura; Hideki Oizumi; Hiroyasu Tanaka; Toshiaki Takahashi; Masaru Yoshioka; Ken-ichi Nagamatsu; Atsushi Takeda (Brain Disorders)
Background: 123I-FP-CIT, primarily used for imaging dopamine transporters in the nigrostriatal pathway, also shows some affinity for the serotonin transporter (SERT), which is predominantly distributed in the raphe nuclei in the brainstem. Recent imaging studies have demonstrated that compared with Parkinson's disease (PD), atypical parkinsonian syndromes (PS) exhibit pronounced SERT reduction using semiquantitative methods. However, the utility of qualitative visual assessment methods for SERT has been poorly discussed to date. Objectives: The aims of this study were to propose a visual assessment grading system of brainstem 123I-FP-CIT uptake and investigate the ability of this method to differentiate PD from PS. Methods: We analyzed the imaging data of 97 parkinsonian patients who underwent 123I-FP-CIT SPECT. First, we graded 123I-FP-CIT uptake in the midbrain and pons with a 4-degree scale and analyzed the interrater agreement of our grading method. Next, we compared the visual grading data of the PD (n = 59) and PS (n = 11) groups and analyzed the diagnostic utility of the qualitative visual assessment method. Results: The interrater agreement of the visual grading of 123I-FP-CIT uptake among the three raters was moderate (Fleiss’ Kappa 0.480 for midbrain, 0.488 for pons). The patterns of 123I-FP-CIT uptake in the pons differed significantly between patients with PD and PS (p = 0.035). The visual assessment-based classification showed 81.8 % sensitivity, 61.0 % specificity, 28.1 % positive predictive value, and 94.7 % negative predictive value in distinguishing PS from PD. Conclusions: Visual assessment of SERT abnormalities with 123I-FP-CIT may contribute to differentiating PD and PS in clinical settings.